DUAL-BAND READER WITH POLARIZATION PROCESSING SIGNALS OF THE BACKSCATTERING WAVES OF THE RADIO IDENTIFICATION TAG - A. A. Popov; T. N. Parfenovich; V. B. Kirilchyk; D. V. Gololobov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Based on frequency and polarization structure analysis of electromagnetic field and variants of RFID convertors design the structure scheme of two bands reader with polarization processing is proposed. Advantages of technical model with opportunity of identification of many classes RFID tags are shown.